1972
DOI: 10.1017/s002572730001749x
|View full text |Cite
|
Sign up to set email alerts
|

Osler Transmitted--a Study in Humanism

Abstract: ALFRED WHITE FRANKLIN THE PLAN of my oration is to consider three questions, by whom is Osler transmitted, by what means and to what end? And because Osler is praised as a humanist, we shall need to examine that chameleon word, on our way to the finish that crowns the work-the moral. My title, Osler transmitted, well understood by Oslerolators, comes from Osler's classification of authors as Creators, Transmuters and Transmitters when opening the Bodley Shakespeare Exhibition in Oxford on 24 April 1916. He ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…52 Even AW Franklin (1905–1984), a warm admirer of Osler, suggested that hehad a kindly regard for the less privileged person but, [as] a man of his time, he had no general sympathy for the poor who are always with us, to excite pity and solicitude but not to be inspirers of social action. 53 However, the testimony of those who knew of Osler’s work in the Ewelme Almshouse does not accord with Franklin’s suggestion, and while Patrick Mallam (1900–1973), son of one of Osler’s colleagues at the Radcliffe Infirmary, may have been correct when he wrote that the Regius, “as titular landlord”, regarded the two Almshouse families with Friedreich’s Ataxia and Alkaptonuria “kindly and almost as a collection of esoteric incunabulae to show his medical friends”, Osler was, as Franklin acknowledged, a man of his time and such attitudes remained common throughout much of the twentieth century. When speaking of Sir Thomas Browne (1605–1682), Osler himself reminded his audience that “… a man must be judged by his times and his surroundings”.…”
Section: The Oslers At Ewelmementioning
confidence: 99%
See 1 more Smart Citation
“…52 Even AW Franklin (1905–1984), a warm admirer of Osler, suggested that hehad a kindly regard for the less privileged person but, [as] a man of his time, he had no general sympathy for the poor who are always with us, to excite pity and solicitude but not to be inspirers of social action. 53 However, the testimony of those who knew of Osler’s work in the Ewelme Almshouse does not accord with Franklin’s suggestion, and while Patrick Mallam (1900–1973), son of one of Osler’s colleagues at the Radcliffe Infirmary, may have been correct when he wrote that the Regius, “as titular landlord”, regarded the two Almshouse families with Friedreich’s Ataxia and Alkaptonuria “kindly and almost as a collection of esoteric incunabulae to show his medical friends”, Osler was, as Franklin acknowledged, a man of his time and such attitudes remained common throughout much of the twentieth century. When speaking of Sir Thomas Browne (1605–1682), Osler himself reminded his audience that “… a man must be judged by his times and his surroundings”.…”
Section: The Oslers At Ewelmementioning
confidence: 99%
“…had a kindly regard for the less privileged person but, [as] a man of his time, he had no general sympathy for the poor who are always with us, to excite pity and solicitude but not to be inspirers of social action. 53…”
Section: The Oslers At Ewelmementioning
confidence: 99%
“…A few admiring Oslerians ventured to point out chinks in their hero’s armour. Thus, in 1972, Alfred White Franklin (1905–1984), co-founder of the OCL with Walter Reginald Bett (1903–1968), suggested that Osler ‘had a kindly regard for the less privileged person but, [as] a man of his time, … had no general sympathy for the poor …’ 6 In 1973, George T Harrell (1908–1999) of the AOS reported on Osler’s sometimes-exorbitant consultation fees. 7 In 1974, AOS member Charles G Roland (1933–2009) critiqued ‘Osler’s rough edge’, noting: ‘Occasionally I find Osler too good to be true’.…”
mentioning
confidence: 99%
“…it was through him that the international medical wheels turned with an easy movement'. 4 Wilburt C Davison (1892-1972, after reading some 440 articles about Osler, observed that 'none of his students would brook any criticism about him', adding: 'We regarded him as perfect'. 5 'Second-generation' Oslerians included inaugural members of the Osler Club of London, founded in 1928, and later the American Osler Society (AOS), founded in 1970, which was about the same time 'humanism in medicine' became a cause ce´le`bre for those alarmed about the unintended consequences of technology in health care.…”
mentioning
confidence: 99%
See 1 more Smart Citation